2011
DOI: 10.1108/11766091111162098
|View full text |Cite
|
Sign up to set email alerts
|

Convergence versus divergence of performance measurement systems

Abstract: Purpose -The purpose of this paper is to report on two institutional change scenarios of performance measurement (PM) systems, namely, subversion and integration. Subversion represents insiders' use of existing institutional logic whereas integration represents insiders' use of imported institutional logic. Design/methodology/approach -The scenarios are drawn from two case studies: BAE Systems (a large UK manufacturing company) and Alpha (a medium-sized Sri Lankan manufacturing company). The data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 42 publications
(49 reference statements)
1
39
0
Order By: Relevance
“…QRAM has no theoretical bias, and over the first ten years of its publishing life various authors have adopted an array of theories, most commonly as a lens to assist the interpretation of longitudinal case studies. The theories that have been used to date, but in no particular order, include: institutional theory (Abrahamsson and Gerdin, 2006;Jazayeri et al, 2011;Moilanen, 2008;Rautiainen and Scapens, 2013;Ribeiro and Scapens, 2006), actor-network theory (Hansen, 2011;Rautiainen and Scapens, 2013;Voselman, 2012), structuration theory (Busco and Scapens, 2011), Foucault's govenmentality (Jakobsen, 2012), Schein's theory of culture (Busco and Scapens, 2011), transaction cost economics (Vosselman, 2012) and contingency theory (Porporato, 2009). Some articles in QRAM have also combined more than one theoretical approach in an attempt to draw out richer analysis and interpretation of empirical observationse.g., Rautiainen and Scapens' (2013) combination of actor-network theory and new institutional sociology, Vosselman's (2012) fusion of transaction cost economics and actor-network theory, and Busco and Scapens' (2011) combined use of Schein's culture theory and Giddens' structuration approach.…”
Section: Theory In Qualitative Management Accounting Researchmentioning
confidence: 99%
“…QRAM has no theoretical bias, and over the first ten years of its publishing life various authors have adopted an array of theories, most commonly as a lens to assist the interpretation of longitudinal case studies. The theories that have been used to date, but in no particular order, include: institutional theory (Abrahamsson and Gerdin, 2006;Jazayeri et al, 2011;Moilanen, 2008;Rautiainen and Scapens, 2013;Ribeiro and Scapens, 2006), actor-network theory (Hansen, 2011;Rautiainen and Scapens, 2013;Voselman, 2012), structuration theory (Busco and Scapens, 2011), Foucault's govenmentality (Jakobsen, 2012), Schein's theory of culture (Busco and Scapens, 2011), transaction cost economics (Vosselman, 2012) and contingency theory (Porporato, 2009). Some articles in QRAM have also combined more than one theoretical approach in an attempt to draw out richer analysis and interpretation of empirical observationse.g., Rautiainen and Scapens' (2013) combination of actor-network theory and new institutional sociology, Vosselman's (2012) fusion of transaction cost economics and actor-network theory, and Busco and Scapens' (2011) combined use of Schein's culture theory and Giddens' structuration approach.…”
Section: Theory In Qualitative Management Accounting Researchmentioning
confidence: 99%
“…Interestingly, only three papers (Di Giuli et al, 2011;Hiebl, 2015) on finance managers in family firms were published in finance journals. Indeed, with eight papers (Filbeck and Lee, 2000;Gallo and Vilaseca, 1998;Gallo et al, 2004;Gordini, 2016;Gurd and Thomas, 2012 Jazayeri et al (2011) contains two cases: one from the UK and one from Sri Lanka. However, only the Sri Lankan case is referred to in the present paper, as only this case was highlighted by Jazayeri et al (2011) as constituting a family firm, while the case firm from the UK can be classified as a non-family firm Hamilton, 1992;Hiebl, 2013a;Songini et al, 2015), family business and entrepreneurship journals appear to be the most frequent outlets for research on finance managers in family firms.…”
mentioning
confidence: 99%
“…Indeed, with eight papers (Filbeck and Lee, 2000;Gallo and Vilaseca, 1998;Gallo et al, 2004;Gordini, 2016;Gurd and Thomas, 2012 Jazayeri et al (2011) contains two cases: one from the UK and one from Sri Lanka. However, only the Sri Lankan case is referred to in the present paper, as only this case was highlighted by Jazayeri et al (2011) as constituting a family firm, while the case firm from the UK can be classified as a non-family firm Hamilton, 1992;Hiebl, 2013a;Songini et al, 2015), family business and entrepreneurship journals appear to be the most frequent outlets for research on finance managers in family firms. Furthermore, with three papers (Hiebl, 2013b(Hiebl, , 2014aLutz and Schraml, 2012) and two papers (Amat et al, 1994;Jazayeri et al, 2011), respectively, general management and accounting journals were also found to be outlets for research on such managers.…”
mentioning
confidence: 99%
See 2 more Smart Citations